Assessing the genetic and chemical diversity of Taraxacum species in the Korean Peninsula. (January 2021) - Lee, Yun Sun; Kim, Jinkyung; Woo, Sunmin; Park, Jee Young; Park, Hyun-Seung; Shim, Hyeonah; Choi, Hong-Il; Kang, Jung Hwa; Lee, Taek Joo; Sung, Sang Hyun; Yang, Tae-Jin; Kang, Kyo Bin
Abstract: The genetic relationship between Taraxacum species, also known as the dandelion, is complicated because of asexual and mixed sexual apomictic reproduction. The usage of Taraxacum species in traditional medicines make their specialized metabolism important, but interspecific chemical difference has rarely been reported for the genus. In this study, we assembled the chloroplast genome and 45S rDNA of six Taraxacum species that occur in Korea ( T. campylodes, T. coreanum, T. erythrospermum, T. mongolicum, T. platycarpum, and T. ussuriense ), and performed a comparative analysis, which revealed their phylogenetic relationships and possible natural hybridity. We also performed a liquid chromatography–mass spectrometry-based phytochemical analysis to reveal interspecific chemical diversity. The comparative metabolomics analysis revealed that Taraxacum species could be separated into three chemotypes according to their major defensive specialized metabolites, which were the sesquiterpene lactones, the phenolic inositols, and chlorogenic acid derivatives. The CP DNA- and 45S rDNA-based phylogenetic trees showed a tangled relationship, which supports the notion of ongoing hybridization of wild Taraxacum species. The untargeted LC–MS analysis revealed that each Taraxacum plant exhibits species-specific defensive specialized metabolism. Moreover, 45S rDNA-based phylogenetic tree correlated with the hierarchical cluster relied on metabolite compositions. Given the coincidence between these analyses, we represented that 45S rDNA could well reflect overall nuclear genome variation in Taraxacum species. Graphical abstract: Image 1 Highlights: Phylogenetic relationship between six Taraxacum species was supposed based on chloroplast genome and 45 S rDNA assembly. Interspecific chemical diversity was investigated using LC–MS. Taraxacum species exhibit species-specific defensive specialized metabolism. Phylogeny based on 45 S rDNA sequence correlated with the phylochemical relationship.